Demonstration and STEM Analysis of Ferroelectric Switching in MOCVD‐Grown Single Crystalline Al0.85Sc0.15N - Niklas Wolff; Georg Schönweger; Isabel Streicher; Md Redwanul Islam; Nils Braun; Patrik Straňák; Lutz Kirste; Mario Prescher; Andriy Lotnyk; Hermann Kohlstedt; Stefano Leone; Lorenz Kienle; et al. (Advanced Physics Research, 2024)
Abstract Wurtzite‐type Al1−xScxN solid solutions grown by metal organic chemical vapor deposition are for the first time confirmed to be ferroelectric. The film with 230 nm thickness and x = 0.15 exhibits a coercive field of 5.5 MV cm−1 at a measurement frequency of 1.5 kHz. The single crystal quality and homogeneous chemical composition of the film are confirmed by X‐ray diffraction and spectroscopic methods such as time of flight secondary ion mass spectrometry. Annular bright field scanning transmission electron microscopy serves to prove the ferroelectric polarization inversion at the unit cell level. The single crystal quality further allows to image the large‐scale domain pattern of a wurtzite‐type ferroelectric for the first time, revealing a predominantly cone‐like domain shape along the c‐axis of the material. As in previous work, this again implies the presence of strong polarization discontinuities along this crystallographic axis, which can be suitable for current transport. The domains are separated by narrow domain walls, for which an upper thickness limit of 3 nm is deduced but which can potentially be atomically sharp. The authors are confident that these results will advance the commencement of the integration of wurtzite‐type ferroelectrics to GaN as well as generally III‐N‐based heterostructures and devices.